Adaptations to sea level change and transitions to agriculture at Khao Toh Chong rockshelter, Peninsular Thailand. (January 2017) - Marwick, Ben; Van Vlack, Hannah G.; Conrad, Cyler; Shoocongdej, Rasmi; Thongcharoenchaikit, Cholawit; Kwak, Seungki
Abstract: This study reports on an analysis of human adaptations to sea level changes in the tropical monsoonal environment of Peninsula Thailand. We excavated Khao Toh Chong rockshelter in Krabi and recorded archaeological deposits spanning the last 13, 000 years. A suite of geoarchaeological methods suggest largely uninterrupted deposition, against a backdrop of geological data that show major changes in sea levels. Although there is a small assemblage of mostly undiagnostic ceramics and stone artefacts, there are some distinct changes in stone artefact technology and ceramic fabric. There is a substantial faunal assemblage, with changes in both the mammalian and shellfish taxa during the Pleistocene-Holocene transition that correlate with local sea level fluctuation. This assemblage provides an opportunity to explore subsistence behaviours leading up to the transition to the Neolithic. We explore the implications for current debates on the prehistoric origins of agricultural subsistence in mainland Southeast Asia. The data highlight the importance of local contingencies in understanding the mechanisms of change from foragers to agriculturalists. Highlights: An archaeological site from peninsular Thailand including the 'missing millennia' is described. Geoarchaeological analysis indicate a relatively intact deposit. The faunal assemblage changes with local sea level changes. Changes in subsistence behaviours are strongly locally contingent.